Micropropagação e etnobotânica de espécies de Bromeliaceae nativas de Sergipe - Santana, Daniela Maria Andrade (2018)
Bromeliaceae are characterized as ornamental plants par excellence and are composed of 3,248 species among 58 genera. They are an important taxonomic group, both on the economic scenario - where they impress the ornamental market due to its exotic forms - and in the ecological scenario, in which they are considered amplifiers of the biodiversity. However, Bromeliaceae is currently the second most endangered botanical family. Therefore, the development of ornamental bromeliad cultivation techniques has been considered an important conservation strategy. In the light of the foregoing, the main objective of this research is to apply micropropagation techniques in native Bromeliaceae species with ornamental potential of Sergipe and to carry out their ethnobotanical study, as a form of valorization and conservation. Considering the ecological importance played by the Bromeliaceae family in the Restinga ecosystems, like as their high degree of endemism in these environments, the research was held in a Restinga area located in Aguilhadas community, located in the city of Pirambu, east of Sergipe. From where the mature fruits of Bromeliaceae Aechmea aquilega and Hohenbergia catingae were collected from adult plants in a natural population. The technique used was the propagation through seed germination in vitro, through which three experiments were realized with the bromeliads H. catingae and A. aquilega. The first experiment, in order to analyze the disinfestations of seeds of H. catingae in different times of immersion in sodium hypochlorite. The second experiment evaluated the germination of A. aquilega in medium supplemented culture with the concentrations of 15 g L-¹ and 30 g L-¹ of sucrose. And the third, who investigated the germination of A. aquilega in two levels of maturation of its seeds. The variables analyzed were the Germination Speed Index (IVG) and the Percent Germination. The results showed that the most effective disinfestations was the one with immersion time in the sodium hypochlorite for 20 minutes, segmented in two ten minute periods. For the germination of A. aquilega, it was observed that the culture medium with 15 g L-¹ sucrose is sufficient in germination in vitro. In the third experiment it was verified that the seeds of A. aquilega, in the two stages of maturation, did not differ in the percentage of germination and the IVG. However, in relation to the length of the air component and number of leaves, the treatment that had seeds with less degree of maturation obtained the best results. The etonobotanical study was developed with 20 people from the Aguilhadas community. The sociocultural profile of the interviewees was traced and the knowledge and use of the Bromeliaceae species was analyzed. The approximation of the community by the cultivation of ornamental plants was identified. However, the local population is unaware of the use of bromeliads as ornamental plants. This causes a devaluation of these species, facilitating their extractivism and / or deforestation.